Analisis Spasial Faktor Prioritas Daerah Rawan Banjir di Kota Denpasar Provinsi Bali - DEWA AYU CHYNTIA ANGELINA; NI MADE TRIGUNASIH; PUTU PERDANA KUSUMA WIGUNA; I WAYAN SEDANA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Analysis Priority Factors of Flood Prone Areas in Denpasar City Bali Province Floods are caused by the low infiltration capacity of the soil and the overflow of surface water (runoff) due to the long duration of rain and the high intensity of rainfall so that it cannot accommodate the accumulation of rainwater. Denpasar City is one of the cities in Bali Province where floods often cause losses in terms of material and physical environment. The determinants of flood susceptibility use the same factors, namely rainfall, soil type, land use, slope, and elevation but are influenced by environmental conditions so that the priority value of each factor is different. Therefore, there is a need for a research of the priority factors of flood-prone areas in Denpasar City. The purpose of the research was to determine the determinants of flood vulnerability and priority factors for flood prone areas in Denpasar City using Spatial Multi Criteria Evaluation. This research was carried out in Denpasar City from August to December 2021. The method used was Spatial Multi Criteria Evaluation for weighting and determining priority values ??for determining flood susceptibility through Geographic Information System applications. This research produces an output in the form of a map of each of the determinants of flood vulnerability in Denpasar City. The results showed that the rainfall factor was the first priority, the land use factor was the second priority, the soil type factor was the third priority, the slope factor was the fourth priority, and the altitude factor was the last priority.